Optimal dietary methionine requirement for juvenile sea cucumber Apostichopus japonicus selenka. (10th December 2020) - Li, Bao S.; Han, Xiu J.; Wang, Ji Y.; Song, Zhi D.; Sun, Yong Z.; Wang, Shi X.; Huang, Bing S.
Abstract: This trial was conducted to determine the optimal dietary methionine requirement for juvenile sea cucumber Apostichopus japonicus selenka. Six isonitrogenous and isoenergetic experimental diets were formulated with graded methionine levels (0.18%, 0.37%, 0.57%, 0.78%, 0.96%, 1.10% dry matter). Each diet was assigned randomly to triplicate groups with 30 sea cucumbers juveniles with initial body weight 12.14 g in a recirculated aquaculture system for 56 days. Survival rate was not affected by dietary methionine. With the increase of dietary methionine levels, both weight gain and specific growth rate were significantly increased initially and then decreased afterwards. Both crude protein and crude lipid contents of body wall were evaluated firstly and dropped afterwards. meanwhile, contents of methionine, cystine, aspartic acid and total amino acids of body wall were all increased. Both total antioxidant capacity and total superoxide dismutase activities of intestine were increased, while malondialdehyde contents were decreased with the increase of dietary methionine. All of activities of protease and lipase were increased initially and then decreased afterwards; however, there was no significantly effect on amylase. In conclusion, analysis by a linear regression equation of WG or methionine contents in body wall indicated that the optimum requirement of methionine for juvenile sea cucumber (initial body weight 12.14 g) was 0.58%–0.72% diet (2.77%–3.42% diet protein).